Clozapine: Mechanisms of Toxicity and Side Effects - A. S. Babkina; A. M. Golubev; D. V. Sundukov; A. R. Bashirova; M. A. Golubev (Общая реаниматология)
Clozapine is an atypical antipsychotic agent with a confirmed effectiveness which is widely used in the clinical practice. However, its administration is associated with a high risk of serious adverse events. Life-threatening conditions related to administration of clozapine may be a result of idiosyncrasy, acute poisoning resulting from unintentional overdose of the prescribed dug, suicidal behavior, and criminal actions. The review presents current data on the mechanism of therapeutic and toxic effect of clozapine. It describes the effect of clozapine on cell receptors and ultracellular structures. It dwells on the contribution of major and intermediate metabolites of this medicinal agent to the development of toxic effects.